2012
DOI: 10.1007/s00104-011-2220-7
|View full text |Cite
|
Sign up to set email alerts
|

Forschung als Attraktivitätsparameter für junge Chirurgen

Abstract: Increasing concern has been expressed about the significant shortage of new trainees in surgery. As research in the context of surgical education and training is an essential element of attraction for the field of surgery, there is an urgent priority to implement clear room for research in the concepts of education and training. In this article the relevance of both the thesis accompanying the study and research training during surgical residency for the clinical self-image, personal satisfaction and academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Earlier investigations in orthopedic and trauma departments [14] as well as in general surgery [15] also identified that the incompatibility of clinical and research obligations was the key obstacle to the conduct of research projects in Germany, especially during residency programs. A recent survey among residents in ophthalmology at German university hospitals [16] revealed that 80% were never offered relief from clinical work to pursue their scientific activities.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigations in orthopedic and trauma departments [14] as well as in general surgery [15] also identified that the incompatibility of clinical and research obligations was the key obstacle to the conduct of research projects in Germany, especially during residency programs. A recent survey among residents in ophthalmology at German university hospitals [16] revealed that 80% were never offered relief from clinical work to pursue their scientific activities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is considered an opportunity to use qualitative methods to complement high quality quantitative data within a more focused approach. 2,3,18,30,[33][34][35] Therefore, surgical research must consider daily clinical surgery and surgical translational research issues, introducing new techniques and laboratory results in assisting the patient, and require clinical surgeons with competency in research. Consequently, it is necessary to allocate major efforts in developing and maintaining high-quality surgical investigations in academic surgical departments, including individual career-advisory programs and clinical trial centers aiming at attractive academic positions in surgery, and the promotion of translational research, as a benefit to patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Heyo Kroemer, zu dieser Zeit Dekan der Medizinischen Fakultät Göttingen, Dass die Chirurgie ohnehin ein eklatantes Nachwuchsproblem hat, wurde bereits vielfach erörtert [5,12,13,14]. Die Möglichkeit zur Forschung wurde hierbei schon als ein Attraktivitätsparameter der Universitätskliniken hervorgehoben [15]. Im Laufe des Berufslebens scheint sich zudem auch die Motivation für Forschung zu ändern: Das Erlangen neuer Erkenntnisse stellt neben dem Anstreben einer universitären Karriere die höchste Motivation dar.…”
Section: Diskussionunclassified
“…Unter dem Aspekt, die Forschung nicht nur als "Anhängsel" im chirurgischen Alltag zu sehen, wurden bereits verpflichtende Forschungsrotationen nach amerikanischem Vorbild während der Weiterbildungszeit vorgeschlagen [11]. Dies ist insbesondere vor dem Hintergrund zu diskutieren, dass die wissenschaftliche Kompetenz eine solide Grundlage ärztlichen Handelns darstellt [15,24,25,26]. Die Wichtigkeit einer strukturierten Weiterbildung, die auch ein organisiertes wissenschaftliches Arbeiten einschließt, konnte bereits 2010 durch eine Umfrage zur Vereinbarkeit von klinischer und akademischer Entwicklung an orthopädischen und unfallchirurgischen Universitätskliniken gezeigt werden [27].…”
Section: Diskussionunclassified